MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA TEMA 1 PERTUMBUHAN DAN PERKEMBANGAN MAKHLUK HIDUP MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING DAN MEDIA CANVA DI SEKOLAH DASAR - Muhammad Faruq Dzulfiqar Daenuri; Sandi Budiana (STKIP Subang, 2023)
The purpose of this study was to improve student learning outcomes by using the Problem Based Learning learning model for class III-C students at SDN Kawungluwuk, Bogor City in the first semester of the 202/2024 school year. The research used is Collaborative Classroom Action Research (PTKK) which is descriptive qualitative using a qualitative approach and validated using a quantitative approach by collecting data at SDN Kawungluwuk, Bogor City. The subject of this research is class III-C students of SDN Kawungluwuk, Bogor City, totalling 28 people. The object of this research is the improvement of students' learning outcomes on theme 1: Growth and Development of Living Things in mathematics subjects using the Poblem Based Learning model and the use of Canva media. This research was conducted in two cycles and through four stages that included planning, implementation, observation and reflection. Data obtained through observation, reflection. Data is obtained through observation, learning implementation, direct tests and documentation. The results of this study indicate that the application of the Problem Based learning model can improve student learning outcomes. The increase in student learning outcomes can be measured from the evaluation results of cycle I and cycle II with an increase in student learning outcomes that have met the achievement of learning outcomes, namely in cycle I by 43% (12 students) and in cycle II by 82% (23 students). The results of research in class III-C at SDN Kawungluwuk, Bogor City have been achieved well, namely there is an increase in learning outcomes by applying the Problem Based Learning learning model and the use of canva media.